2021
DOI: 10.3126/nmcj.v23i3.40380
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation of Common Carotid Artery in Relation to Vertebral Level in Nepalese: A Cadaveric Study

Abstract: The principal arterial supply of the head and neck are the two Common Carotid Arteries (CCA), they ascend in the neck and each divides into two branches, the External Carotid Artery (ECA) supplying the exterior of the head, neck and the Internal Carotid Artery (ICA) supplying the cranial and orbital cavities. Atherosclerosis of the carotid arteries is a major cause of stroke and transient ischemic attack and it increases with age. The present study was observational based descriptive type, conducted to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In contrary previous studies showed that there is no bifurcation of CCA at the normal levels, and the most common level was observed at the C4 level, followed by C3 levels [25]. Similarly, many cadaveric studies were done, and their normal level of bifurcation was observed by various authors: 75% [26], 63.15 [27], 48.3% [28], 56.76% [29], 57.5% [30], 22.5% [31], 39% [32], 57% [33], 32.14% [34], 77% [35], 68.72% [36], and 83.75% [37]. In addition, the high and low level of bifurcation was also noted.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In contrary previous studies showed that there is no bifurcation of CCA at the normal levels, and the most common level was observed at the C4 level, followed by C3 levels [25]. Similarly, many cadaveric studies were done, and their normal level of bifurcation was observed by various authors: 75% [26], 63.15 [27], 48.3% [28], 56.76% [29], 57.5% [30], 22.5% [31], 39% [32], 57% [33], 32.14% [34], 77% [35], 68.72% [36], and 83.75% [37]. In addition, the high and low level of bifurcation was also noted.…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, high-level and low-level bifurcation is noted in 36% and 56% of CT images, respectively. Similarly, many studies were done in cadaver and CT images, 24.75% [26], 48.3, 5% [28], 63.8%, 13.75% [31], 42%, 1% [33], 8%, 5% [35], 37.5% [36], and 46.5%, 42.3% [38].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the lowest AM in our study was at C4, which was lower than those found in previous studies and could result in the CB becoming much more difficult to access in HCB cases. Most prior studies regarded HCB as CB located above the vertebral body of C3 [ 2 , 13 15 ]. Based on this description, we discovered that the occurrence of HCB was as high as 10.47%, which is comparable to prior research employing the same method (CTA) in living Thai people [ 2 ], but with a lower percentage than the 19.2% observed in a Japanese cadaveric study [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the C3 vertebra has been employed as the gold standard landmark to differentiate between "high" and "low" carotid bifurcations [ 2 , 13 15 ]. However, our data draws attention to the possible inadequacies of relying solely on the C3 as a consistent landmark.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation